4^(1+log(x^2+y^2)*1/log(4))=20 sqrt(log(3))*(x^2-y^2)-2=0

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:

Решение

Вы ввели
[TeX]
[pretty]
[text]
        / 2    2\     
     log\x  + y /     
 1 + ------------     
        log(4)        
4                 = 20
$$4^{\frac{\log{\left (x^{2} + y^{2} \right )}}{\log{\left (4 \right )}} + 1} = 20$$
  ________ / 2    2\        
\/ log(3) *\x  - y / - 2 = 0
$$\left(x^{2} - y^{2}\right) \sqrt{\log{\left (3 \right )}} - 2 = 0$$
Численный ответ
[pretty]
[text]
x1 = -1.858511388719478
y1 = -1.243356512831295
x2 = -1.858511388719478
y2 = 1.243356512831295
x3 = 1.858511388719478
y3 = 1.243356512831295